Complications of colonoscopy in elderly patients (Revista Argentina de Cirugía, 2021)
Background: For the World Health organization, elderly persons are those > 60 years, and classifies this age group in three sub-groups: the elderly (60-74 years), the old (75-90 years) and the long-lived (> 90 years). Patients > 80 years undergoing a colonoscopy for diagnosis or follow-up of colorectal cancer are believed to be at higher risk of complications.Objective: The aim of this study is to analyze the incidence of complications of colonoscopy by age. Material and methods: We conducted a retrospective analysis of a consecutive series of adult patients undergoing colonoscopy in three institutions between January 2005 and June 2017. All the complications occurring within 30 days of the procedure were recorded. Gastrointestinal complications included perforation, bleeding, transfusions, bloating, nausea, vomiting and abdominal pain. Dehydration, myocardial infarction and angina were non-gastrointestinal complications. The variables were compa- red using the Fisher’s exact test with Yates correction or the chi square test, as applicable. A p < 0.05 was considered statistically significant.Results: Of a total of 11,746 colonoscopies, 11,042 were analyzed (704 were lost to follow-up). There were 239 patients > 80 years, 4070 between 60 and 80 years and 7437 < 60 years; 57.8% (n = 6800) were diagnostic procedures, 2222 were performed in > 60 years and 99% were outpatient procedures. Fifteen procedures were cancelled due to intolerance to anesthesia. One patient presented atrial fibrillation with no clinical relevance. There were no major adverse events. Complications occurred in 14 patients (0.12%), 6 in therapeutic procedure (0.05%),
Keywords: colonoscopy; complication; endoscopy; elderly; screening